Diaphragm, preparation method thereof, battery and electric equipment

By designing a second coating with asymmetric pore size distribution on the lithium-ion battery separator, the problem of lack of liquid on the negative electrode plate side during the battery cycle is solved, and the battery cycle performance is improved and the life span is extended.

CN119447704APending Publication Date: 2025-02-14HUAWEI TECH CO LTD +1
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202310953462.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-07-31
Publication Date
2025-02-14

AI Technical Summary

Technical Problem

During the circulation process of lithium-ion batteries, SEI film is repeatedly generated on the surface of the negative electrode sheet, resulting in the consumption of electrolyte, which in turn causes the separator to be dehydrated near the negative electrode side, affecting the battery cycle life.

Method used

A diaphragm is designed, which consists of a base film, a first coating and a second coating. The pore size distribution of the second coating is larger than that of the first coating to ensure that the electrolyte is enriched on the second coating side. Uniform pores are formed on the layer side to maintain good lyophilic properties.

Benefits of technology

Through the asymmetric pore size distribution of the second coating, the electrolyte is always wetted by the separator, avoiding the problem of electrolyte breaking the bridge, extending the cycle life of the battery and improving the cycle performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119447704A_ABST
    Figure CN119447704A_ABST
Patent Text Reader

Abstract

The invention provides a diaphragm, a preparation method thereof, a battery and electric equipment. The diaphragm comprises a base membrane, a first coating and a second coating, wherein the first coating and the second coating are respectively arranged on two sides of the base membrane. The pore size distribution eta (2) of the second coating and the pore size distribution eta (1) of the first coating meet the condition that eta (2) / eta (1) is greater than 1.0. The diaphragm can improve the cycle performance of the battery and prolong the cycle life of the battery.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of batteries, and in particular to a diaphragm and a preparation method thereof, as well as a battery and an electrical device. Background Art

[0002] Rechargeable batteries, such as lithium-ion batteries, have been widely used in consumer terminals such as mobile phones, notebooks, wearables, mobile power supplies and other products. They also have broad application prospects in the fields of electric vehicles and energy storage. As one of the four main materials of the battery, the diaphragm is not only a safety medium, but also a transmission channel for the electrolyte and a bridge between the positive and negative electrodes. The lithium ions in the electrolyte shuttle back and forth between the positive and negative electrodes through the porous structure of the diaphragm. The higher the shuttle efficiency, the longer the cycle life of the battery cell. Therefore, both sides of the diaphragm need to have good hydrophilic properties. However, SEI film will be repeatedly generated on the surface of the negative electrode material during the cycle, thereby continuously consuming the electrolyte. Therefore, the diaphragm close to the negative electrode side is more likely to be depleted, which will then form a broken bridge of electrolyte between the negative electrode and the diaphragm, causing the battery cycle life to decay. Summary of the invention

[0003] The present application provides a diaphragm and a preparation method thereof, as well as a battery and an electrical device to improve the cycle performance of the battery and extend the cycle life of the battery.

[0004] In a first aspect, the present application provides a diaphragm, which includes a base film, a first coating layer and a second coating layer, wherein the first coating layer and the second coating layer are respectively disposed on both sides of the base film. The pore size distribution η of the second coating layer is (2) The pore size distribution η of the first coating (1) Satisfy: η (2) / η (1) >1.0, where η (1) =[D90 (1) -D25 (1) ] / D50 (1) , η (2) =[D90 (2) -D25 (2) ] / D50 (2) ;

[0005] D25 (1) It indicates the pore size corresponding to when the volume percentage of the cumulative pore size distribution in the first coating reaches 25%;

[0006] D50 (1) It indicates the pore size corresponding to when the volume percentage of the cumulative pore size distribution in the first coating reaches 50%;

[0007] D90 (1) It indicates the pore size corresponding to when the volume percentage of the cumulative pore size distribution in the first coating reaches 90%;

[0008] D25 (2) It indicates the pore size corresponding to when the volume percentage of the cumulative pore size distribution in the second coating reaches 25%;

[0009] D50 (2) It indicates the pore size corresponding to when the volume percentage of the cumulative pore size distribution in the second coating reaches 50%;

[0010] D90 (2) It indicates the pore size corresponding to when the volume percentage of the cumulative pore size distribution in the second coating reaches 90%.

[0011] In the diaphragm of the present application, when there is a difference in the pore size distribution between the first coating and the second coating and the pore size distribution of the second coating is larger than that of the first coating, the electrolyte is more likely to accumulate on the side of the second coating, so that the second coating stores more electrolyte relative to the first coating. The first coating side forms uniform pores with good lyophilicity and heat resistance, and the second coating side forms pores of both large and small sizes and with a wide distribution. The small pores are used to transmit the electrolyte, and the large pores are used to store the electrolyte. When assembling the battery, the second coating is arranged toward the negative electrode plate. During the charge and discharge cycle of the battery, both the first coating and the second coating have high lyophilicity, and the second coating can enrich more electrolyte to effectively solve the problem of lack of liquid caused by repeated generation of SEI film on the negative electrode plate side. Since the second coating can always maintain a high lyophilicity, the problem of electrolyte bridging in the second coating can be avoided in the later stage of the battery cycle, so that the diaphragm always plays the role of electrolyte transmission channel, improves the cycle performance of the battery, and extends the cycle life of the battery.

[0012] In an optional implementation, the pore size D90 of the second coating is (2) Larger than the pore size D90 of the first coating (1) When the pore size of the second coating is larger than that of the first coating, the electrolyte is more likely to be enriched in the second coating during the battery manufacturing process. In the later stage of the battery cycle, the electrolyte enriched in the second coating can continuously replenish the consumption of the electrolyte, thereby improving the cycle performance of the battery.

[0013] In an optional embodiment, the pore size D90 of the first coating is (1) The pore size D90 of the second coating is less than 0.8 μm. (2) Greater than or equal to 0.5μm. When the pore size D90 in the first coating (1) Less than 0.8μm, pore size D90 of the second coating (2) When the thickness is greater than or equal to 0.5 μm, both the first coating and the second coating can obtain higher liquid retention performance, so that the diaphragm is always infiltrated with electrolyte during the battery charge and discharge cycle, ensuring that the active ions of the battery can shuttle in the diaphragm.

[0014] In an optional embodiment, the pore size D90 of the first coating is (1) The pore size D90 of the second coating is 0.1-0.5 μm. (2) When the pore size of the first coating layer and the second coating layer is limited to the above size, the first coating layer and the second coating layer can respectively have a higher electrolyte retention capacity, and at the same time, the first coating layer and the second coating layer themselves will not form a broken bridge due to the excessive pore size, thereby affecting the transmission of lithium ions.

[0015] In an optional implementation, the n (2) / η (1) The value is 1.2 to 3. The greater the difference in pore size distribution between the first coating and the second coating, the more electrolyte the second coating can always store, and the lower the possibility of subsequent liquid deficiency on the second coating side, so as to prevent the battery cycle life from being affected by liquid deficiency on the negative electrode side of the battery. At the same time, the pore size distribution of the first coating and the second coating cannot be too large, otherwise, overly large pores are likely to appear in the second coating, thereby affecting the contact between the second coating and the electrolyte.

[0016] In an optional implementation, both the first coating and the second coating include an organic resin; wherein the mass content of the organic resin in the first coating is less than 50%, and the mass content of the organic resin in the second coating is greater than the mass content of the organic resin in the first coating. When the content of the organic resin in the second coating is high, it is beneficial for the second coating to form a suitable pore size distribution. When the content of the organic resin in the first coating is low, it is beneficial for the first coating to form small pores with uniform pore sizes.

[0017] In an optional implementation, the mass content of the organic resin in the first coating is 10-30%, and the mass content of the organic resin in the second coating is 20-80%. When the organic resin content in the first coating is 10-30%, in addition to helping the first coating to form fine and uniform pores, it can also ensure that the first coating has high stability, making it difficult for the first coating to fall off from the base film, and at the same time, the first coating can have suitable heat resistance. When the organic resin content in the second coating is 20-80%, the second coating can be controlled by process to form pores with large pores and wide pore size distribution, and at the same time, the second coating can have high adhesion stability and thermal stability with the base film.

[0018] In an optional implementation, the organic resin content in the second coating is 1.2 to 5 times the organic resin content in the first coating. When the organic resin content in the first coating and the second coating satisfies the above relationship, the diaphragm can have both suitable pore size distribution and high heat resistance, and an asymmetric distribution of pore sizes on both sides of the diaphragm can be achieved. Preferably, the organic resin content in the second coating is 1.5 to 4 times the organic resin content in the first coating. By optimizing the content of organic resin in the first coating and the second coating, the pore size distribution and heat resistance of the diaphragm can be further optimized.

[0019] In an optional implementation, both the first coating and the second coating include inorganic particles; the particle size D50 of the inorganic particles in the first coating is 0.05-0.6 μm, preferably 0.1-0.4 μm. When the particle size of the inorganic particles in the first coating is within the above numerical range, a uniform and dense ceramic coating can be formed by combining with a specific content of organic resin. At the same time, the organic resin is distributed in a network-like manner between the particles of the inorganic particles, thereby ensuring that the pores formed in the first coating are relatively uniform, so that the first coating has good thermal shrinkage performance and a higher film breaking temperature.

[0020] In addition, the particle size D50 of the inorganic particles in the second coating is 0.2 to 2 μm, preferably 0.3 to 1.3 μm. The inorganic particles of the above particle size in the second coating are combined with a specific content of organic resin in the second coating to more easily form a suitable pore size distribution, with abundant small pores for transmitting electrolyte and suitable large pores for storing electrolyte, so that the diaphragm is always in contact with the electrolyte during the charge and discharge cycle of the battery.

[0021] In an optional implementation, the particle size D50 of the inorganic particles in the second coating layer is 1.5 to 5 compared to the particle size D50 of the inorganic particles in the first coating layer. When the particle size ratio of the inorganic particles in the first coating layer to the second coating layer is 1.5 to 5, the diaphragm can have both heat resistance and suitable pore size distribution.

[0022] In a second aspect, the present application provides a method for preparing a diaphragm, the method comprising the following steps:

[0023] A first coating slurry is applied on one side of the base film; a second coating slurry is applied on the other side of the base film; the first coating slurry and the second coating slurry are different slurries;

[0024] The base film coated with the first coating slurry and the second coating slurry is subjected to multi-stage extraction, and then dried to obtain the separator;

[0025] In the obtained diaphragm, the pore size distribution η of the second coating is (2) The pore size distribution η of the first coating(1) Satisfy: η (2) / η (1) >1.0, where η (1) =[D90 (1) -D25 (1) ] / D50 (1) , η (2) =[D90 (2) -D25 (2) ] / D50 (2) ;

[0026] D25 (1) It indicates the pore size corresponding to when the volume percentage of the cumulative pore size distribution in the first coating reaches 25%;

[0027] D50 (1) It indicates the pore size corresponding to when the volume percentage of the cumulative pore size distribution in the first coating reaches 50%;

[0028] D90 (1) It indicates the pore size corresponding to when the volume percentage of the cumulative pore size distribution in the first coating reaches 90%;

[0029] D25 (2) It indicates the pore size corresponding to when the volume percentage of the cumulative pore size distribution in the second coating reaches 25%;

[0030] D50 (2) It indicates the pore size corresponding to when the volume percentage of the cumulative pore size distribution in the second coating reaches 50%;

[0031] D90 (2) It indicates the pore size corresponding to when the volume percentage of the cumulative pore size distribution in the second coating reaches 90%.

[0032] The technical effects that can be achieved in the above-mentioned second aspect can be described with reference to the corresponding effects in the above-mentioned first aspect, and will not be repeated here.

[0033] In an optional implementation, the first coating slurry and the second coating slurry may include organic resins of different weight percentages, or inorganic particles of different weight percentages, or both organic resins of different weight percentages and inorganic particles of different weight percentages. As long as the separator can satisfy η (2) / η (1) >1.0 is enough.

[0034] In an optional implementation, the multi-stage extraction includes three-stage extraction, the mass proportion of the good solvent in the first-stage extraction is 35-60%, the mass proportion of the good solvent in the second-stage extraction tank is 0-35%, and the mass proportion of the good solvent in the third-stage extraction tank is 0-2.5%. In the first-stage extraction, the coating slurry is not completely solidified. By controlling the mass concentration of the good solvent in the first-stage extraction within the range of 35-60%, it can help to form a pore structure with uniform pore size in the thickness direction of the coating. In the second-stage extraction, the coating slurry is completely solidified. By controlling the mass concentration of the good solvent in the second-stage extraction within the range of 20-35%, it can be beneficial to the formation of pores and avoid the formation of a dense coating. By controlling the mass concentration of the good solvent in the third-stage extraction to below 2.5%, it can be used to remove the residual extraction stage on the coated diaphragm.

[0035] In an optional implementation, in the first stage extraction, the concentration of the good solvent gradually decreases from the direction of movement of the base film in the first extraction tank, and the difference between the highest concentration of the good solvent and the lowest concentration of the good solvent in the first extraction tank is 5-15%. Wherein, the multi-stage extraction can be carried out in a multi-stage extraction tank. The multi-stage extraction tank at least includes a first extraction tank, a second extraction tank and a third extraction tank arranged in sequence. In the multi-stage extraction, the base film coated with the coating slurry is extracted in the first extraction tank, the second extraction tank and the third extraction tank in sequence. The first extraction tank is also called a coagulation bath, and the coating slurry coagulates in the first extraction tank. Wherein, along the moving direction of the base film in the first extraction tank, the concentration of the good solvent in the first extraction tank gradually decreases, and the difference between the highest concentration value and the lowest concentration value of the good solvent in the first extraction tank is 5-15wt%, preferably 6-13wt%, and further preferably 7-12wt%. By controlling the above parameters and adopting the formula of the first coating and the second coating, an asymmetric pore structure of the first coating and the second coating can be obtained.

[0036] In an optional implementation, the time for the first stage extraction and the second stage extraction is 5 to 15 seconds respectively.

[0037] Among them, the data in the above-mentioned possible implementation methods of the present application, such as the pore size of the first coating, the pore size of the second coating, the content of organic resin, the particle size of inorganic particles, etc., when measuring, the values ​​within the scope of engineering measurement error should be understood to be within the range specified in the present application.

[0038] In a third aspect, the present application provides a secondary battery, comprising a positive electrode sheet, a negative electrode sheet, and a separator disposed between the positive electrode sheet and the negative electrode sheet, wherein the separator may be the separator of the first aspect of the present application.

[0039] The secondary battery provided by the present application, since it includes the diaphragm of the first aspect of the present application, when the diaphragm of the present application has high heat resistance, the secondary battery of the present application can obtain better safety. At the same time, since the diaphragm of the present application has good air permeability, the secondary battery of the present application can also obtain higher fast charging performance.

[0040] In a fourth aspect, the present application provides an electrical device, which includes the secondary battery of the third aspect of the present application.

[0041] Among them, electrical equipment includes but is not limited to electronic devices, electric vehicles, power storage systems, etc. On the basis that the secondary batteries of each possible implementation method of the present application have good safety and fast charging performance, the electrical equipment using the secondary batteries of the present application as a driving power source can also obtain the same effect. The technical effects that can be achieved in the third and fourth aspects above can be described with reference to the corresponding effects in the first aspect above, and will not be repeated here. BRIEF DESCRIPTION OF THE DRAWINGS

[0042] Figure 1 A schematic diagram of the structure of a battery provided in an embodiment of the present application;

[0043] Figure 2 A schematic diagram of the structure of a diaphragm provided in an embodiment of the present application;

[0044] Figure 3 A schematic diagram of the relative relationship between the pore size distribution diagram of the first coating and the pore size distribution diagram of the second coating according to an embodiment of the present application.

[0045] Reference numerals:

[0046] 11-positive electrode plate; 21-negative electrode plate; 31-diaphragm; 311-base film; 312-first coating layer; 313-second coating layer;

[0047] 314-Inorganic particles. DETAILED DESCRIPTION

[0048] In order to make the objectives, technical solutions and advantages of the present application clearer, the present application will be further described in detail below in conjunction with the accompanying drawings.

[0049] The terms used in the following embodiments are only for the purpose of describing specific embodiments and are not intended to be limiting of the present application. As used in the specification and appended claims of the present application, the singular expressions "a", "an", "above", "the" and "this" are intended to also include expressions such as "one or more", unless there is a clear contrary indication in the context.

[0050] References to "one embodiment" or "some embodiments" etc. described in this specification mean that a particular feature, structure or characteristic described in conjunction with the embodiment is included in one or more embodiments of the present application. Thus, the phrases "in one embodiment", "in some embodiments", "in some other embodiments", "in some other embodiments", etc. that appear at different places in this specification do not necessarily refer to the same embodiment, but mean "one or more but not all embodiments", unless otherwise specifically emphasized in other ways. The terms "including", "comprising", "having" and their variations all mean "including but not limited to", unless otherwise specifically emphasized in other ways.

[0051] Figure 1 Figure 1 is a schematic diagram of the structure of a battery. Figure 1 As shown, the battery includes a positive electrode sheet 11, a negative electrode sheet 21, a separator 31 and an electrolyte. The separator 31 is between the positive electrode sheet 11 and the negative electrode sheet 21. The electrolyte infiltrates the separator 31, the positive electrode sheet 11 and the negative electrode sheet 21. The separator 31 can serve as a transmission channel for active ions and block the conduction of electrons during the charge and discharge cycle of the battery.

[0052] Typically, the negative electrode plate 21 of the battery will repeatedly form an SEI film on its surface during the charge and discharge cycle, thereby continuously consuming the electrolyte. Therefore, in order to avoid the problem of lack of liquid on the surface of the diaphragm 31 close to the negative electrode plate 21, which causes the electrolyte bridge to break between the negative electrode plate 21 and the diaphragm 31, an embodiment of the present application provides a diaphragm 31. The diaphragm 31 of the embodiment of the present application is a diaphragm 31 with a double-sided asymmetric pore size distribution. For a battery assembled with the diaphragm 31, the surface on one side close to the negative electrode plate 21 can have better liquid retention performance, which can alleviate the problem of decreased battery cycle performance due to lack of liquid on the side of the diaphragm 31 facing the negative electrode plate 21.

[0053] Figure 2 Figure 2 is a schematic diagram of the structure of a diaphragm. Figure 2 As shown, the diaphragm 31 includes a base film 311, a first coating 312 is provided on one side of the base film 311, and a second coating 313 is provided on the other side of the base film 311. The base film 311 is a porous film, and its material can be a polyolefin substrate, such as polyethylene or polypropylene. The structure and material selection of the base film 311 are not specifically limited in this application, and it can be a conventional base film 311 in the art. The structures of the first coating 312 and the second coating 313 are described in detail below.

[0054] First coating

[0055] The first coating 312 may include an organic resin. The mass content of the organic resin in the first coating 312 may be less than 50%. The mass content of the organic resin in the first coating 312 is the ratio of the mass of the organic resin to the total mass of the first coating 312. In a preferred embodiment, the mass proportion of the organic resin in the first coating 312 may be, for example, 10 to 30%. This content of organic resin may help to form uniform and fine pores in the first coating 312. Exemplarily, the mass proportion of the organic resin in the first coating 312 may be, for example, 10%, 12%, 14%, 16%, 18%, 20%, 22%, 24%, 26%, 28% or 30% or any value between the above two values.

[0056] The organic resin may be a heat-resistant polymer resin with a melting point or decomposition temperature greater than 200° C., so as to improve the heat resistance of the diaphragm 31, such as the membrane breaking temperature. The organic resin includes, but is not limited to, aromatic polyamide, polyimide, polyamide-imide, polysulfone, polyketone, polyetherketone, polytetrafluoroethylene, etc. The organic resin may also be selected from polymers having adhesive functions, such as at least one of polyvinylidene fluoride and its modified products, polyacrylonitrile, polyacrylate, styrene-butadiene copolymer, etc.

[0057] In addition to the organic resin, the first coating layer 312 may also include inorganic particles 314. The mass content of the inorganic particles 314 in the first coating layer 312 may be greater than 50%. The inorganic particles 314 include, but are not limited to, at least one of SrTiO3, SnO2, Mg(OH)2, MgO, Al(OH)3, Al2O3, SiO2, BaSO4 or TiO2, boehmite, and oxide solid electrolytes (including but not limited to lithium aluminum titanium phosphate, lithium lanthanum tantalate, lithium lanthanum zirconium oxide, etc.). By adding the inorganic particles 314, the heat resistance of the diaphragm 31 can be improved, such as improving the thermal shrinkage performance of the diaphragm 31. In addition, by adding the inorganic particles 314, it is also possible to help form the first coating layer 312 of the desired pore size structure.

[0058] The particle size D50 of the inorganic particles 314 in the first coating layer 312 (1)It can be 0.05 to 0.6 μm, preferably 0.1 to 0.4 μm. For example, the particle size of the inorganic particles 314 in the first coating 312 can be 0.05 μm, 0.1 μm, 0.15 μm, 0.2 μm, 0.25 μm, 0.3 μm, 0.35 μm, 0.4 μm, 0.45 μm, 0.5 μm, 0.55 μm or 0.6 μm or a value between any two of the above values. When the particle size of the inorganic particles 314 in the first coating 312 is within the above numerical range, a uniform and dense ceramic coating can be formed with a specific content of organic resin. At the same time, the organic resin is distributed in a network-like manner between the particles of the inorganic particles 314, thereby ensuring that the pores formed in the first coating 312 are relatively uniform, so that the first coating 312 has good thermal shrinkage performance and a higher film breaking temperature.

[0059] The pore size distribution η of the first coating 312 is (1) =[D90 (1) -D25 (1) ] / D50 (1) , among which D25 (1) D50 represents the pore size corresponding to when the volume percentage of the cumulative pore size distribution in the first coating 312 reaches 25%; (1) D90 represents the pore size corresponding to when the volume percentage of the cumulative pore size distribution in the first coating 312 reaches 50%; (1) It represents the pore size corresponding to when the volume percentage of the cumulative pore size distribution in the first coating layer 312 reaches 90%.

[0060] The pore size D90 of the first coating layer 312 (1) As a preferred embodiment, the pore size D90 of the first coating 312 is (1) The value range of D90 can be 0.1 to 0.5 μm. (1) The value of may be, for example, 0.1 um, 0.2 um, 0.3 μm, 0.4 μm, 0.5 μm, 0.6 μm, or 0.7 μm or any value between any two of the above values. (1) When the pore size D90 of the first coating layer 312 is less than 0.8 μm, especially 0.1 to 0.5 μm, the first coating layer 312 can have a higher lyophilic property, which is conducive to the electrolyte infiltration of the first coating layer 312. (1) The pore size D90 of the first coating 312 cannot be too small, otherwise the air permeability will be poor and the ability to transmit lithium ions will be poor. (1) It should not be too large. If it is too large, the formed coating will be loose and not dense, and the heat resistance will deteriorate. At the same time, the liquid retention capacity of the first coating 312 and the second coating 313 will be differentiated, which will worsen the poor liquid short board effect of the second coating 313.

[0061] The first coating 312 with the above structure can obtain good lyophilicity, electrolyte transport performance and heat resistance. During the battery charge and discharge cycle, the diaphragm 31 is always infiltrated with electrolyte, ensuring that the active ions of the battery can shuttle in the diaphragm 31.

[0062] Second coating

[0063] The second coating 313 may include an organic resin. The mass content of the organic resin in the second coating 313 is greater than the mass content of the organic resin in the first coating 312. The mass content of the organic resin in the second coating 313 is the ratio of the mass of the organic resin to the total mass of the second coating 313. The mass content of the organic resin in the second coating 313 may be greater than or equal to 20%. In a preferred embodiment, the mass proportion of the organic resin in the second coating 313 may be, for example, 20 to 80%. This content of organic resin may help to form pores with a wider pore size distribution range in the second coating 313. Exemplarily, the mass proportion of the organic resin in the second coating 313 may be, for example, 20%, 30%, 40%, 50%, 55%, 58%, 60%, 63%, 65%, 68%, 70%, 72%, 75%, 77% or 80% or any value between the above two values.

[0064] The organic resin in the second coating 313 may be a heat-resistant polymer resin with a melting point or decomposition temperature greater than 200° C. to improve the heat resistance of the diaphragm 31, such as the membrane breaking temperature. The organic resin includes but is not limited to at least one of aromatic polyamide, polyimide, polyamide-imide, polysulfone, polyketone, polyetherketone or polytetrafluoroethylene.

[0065] The organic resin content in the second coating 313 may be 1.2 to 5 times, preferably 1.5 to 4 times, the organic resin content in the first coating 312. When the organic resin content in the first coating 312 and the second coating 313 satisfies the above relationship, the diaphragm 31 can have both a suitable pore size distribution and high heat resistance. By optimizing the content of the organic resin in the first coating 312 and the second coating 313, the asymmetric distribution of the pore size on both sides of the diaphragm 31 can be further optimized, and it can be beneficial to provide the diaphragm 31 with heat resistance.

[0066] In addition to the organic resin, the second coating layer 313 may also include inorganic particles 314. The mass content of the inorganic particles 314 in the second coating layer 313 may be less than 80%. The inorganic particles 314 include, but are not limited to, at least one of SrTiO3, SnO2, Mg(OH)2, MgO, Al(OH)3, Al2O3, SiO2, BaSO4 or TiO2, boehmite, and oxide solid electrolytes (including but not limited to lithium aluminum titanium phosphate, lithium lanthanum tantalate, lithium lanthanum zirconium oxide, etc.). By adding the inorganic particles 314, the heat resistance of the diaphragm 31 can be improved, such as improving the thermal shrinkage performance of the diaphragm 31. In addition, by adding the inorganic particles 314, it is also helpful to form the second coating layer 313 with the desired pore size structure.

[0067] The particle size D50 of the inorganic particles 314 in the second coating layer 313 (2) The inorganic particles 314 in the second coating layer 313 may be 0.2 to 2 μm, preferably 0.3 to 1.3 μm. For example, the particle size of the inorganic particles 314 in the second coating layer 313 may be 0.2 μm, 0.3 μm, 0.4 μm, 0.5 μm, 0.6 μm, 0.7 μm, 0.8 μm, 0.9 μm, 1.0 μm, 1.1 μm, 1.2 μm, 1.3 μm, 1.4 μm, 1.5 μm, 1.6 μm, 1.7 μm, 1.8 μm, 1.9 μm or 2.0 μm or a value between any two of the above values. When the particle size of the inorganic particles 314 in the second coating layer 313 is within the above numerical range, with a specific content of organic resin, pores with a wide pore size distribution can be formed.

[0068] The pore size distribution η of the second coating 313 is (2) =[D90 (2) -D25 (2) ] / D50 (2) , among which D25 (2) D50 represents the pore size corresponding to when the volume percentage of the cumulative pore size distribution in the second coating 313 reaches 25%; (2) D90 represents the pore size corresponding to when the volume percentage of the cumulative pore size distribution in the second coating 313 reaches 50%; (2) It represents the pore size corresponding to when the volume percentage of the cumulative pore size distribution in the second coating layer 313 reaches 90%.

[0069] The pore size D90 of the second coating layer 313 (2) Larger than the pore size D90 of the first coating 312 (1) , so as to generate a driving force between the first coating 312 and the second coating 313, so as to drive the electrolyte to be more easily enriched on the side of the second coating 313 during the preparation of the battery cell. Among them, the pore size D90 of the second coating 313 (2) As a preferred embodiment, the pore size D90 of the second coating 313 is (2)The value range of D90 can be 0.6 to 2 μm. (2) The value of can be, for example, 0.5 μm, 0.6 μm, 0.7 μm, 0.8 μm, 0.9 μm, 1.0 μm, 1.1 μm, 1.2 μm, 1.3 μm, 1.4 μm, 1.5 μm, 1.6 μm, 1.7 μm, 1.8 μm, 1.9 μm or 2.0 μm or a value between any two of the above values. (2) When the thickness is greater than or equal to 0.5 μm, especially when it is 0.6 to 2 μm, the second coating layer 313 can have a higher lyophilic property, which can help the electrolyte to infiltrate the second coating layer 313 .

[0070] The pore size D90 of the second coating 313 is (1) It cannot be too small, otherwise it will be disadvantageous for the electrolyte to be enriched in the second coating 313. On the other hand, the pore size D90 of the second coating 313 is (2) It should not be too large. If it is too large, it is difficult to form a liquid retention space for the electrolyte, and it is easy to form a broken bridge between the second coating 313 and the electrolyte. In the later stage of the cycle, it is not conducive to the adhesion of the electrolyte to the surface of the second coating 313, thereby affecting the cycle performance of the battery.

[0071] In addition, the pore size distribution of the second coating 313 is relatively wide, indicating that the second coating 313 has both small pores and large pores. The small pores in the second coating 313 can form a lithium ion transmission channel for transmitting lithium ions. The large pores in the second coating 313 can be used to absorb and store electrolyte. In the later period of the cycle life of the battery, the electrolyte in the large pores can replenish the electrolyte lost in the small pores, so that the diaphragm 31 can maintain its role as a lithium ion transmission channel, thereby extending the service life of the battery.

[0072] The second coating 313 with the above structure can achieve higher liquid retention performance, so that the diaphragm 31 is always infiltrated with electrolyte during the battery charge and discharge cycle, ensuring that the active ions of the battery can shuttle in the diaphragm 31.

[0073] Figure 3 FIG. 1 is a schematic diagram showing the relative relationship between the pore size distribution diagram of the first coating and the pore size distribution diagram of the second coating in one embodiment. Figure 2 and Figure 3 As shown, there is a certain difference in the pore size distribution between the first coating 312 and the second coating 313. The pore size distribution of the second coating 313 is wider than that of the first coating 312, and the corresponding pore size distribution difference is larger. (2) The pore size distribution η of the first coating 312 (1) Ratio: η (2) / η (1)>1.0, preferably, η (2) / η (1) >1.1, further preferably, η (2) / η (1) The value is 1.2 to 3. The greater the difference in pore size distribution between the first coating 312 and the second coating 313, the greater the difference in electrolyte retention between the first coating 312 and the second coating 313, and the second coating 313 can always store more electrolyte to prevent the battery cycle life from being affected by lack of electrolyte on the negative electrode plate 21 side of the battery. At the same time, the pore size distribution of the first coating 312 and the second coating 313 cannot be too large, otherwise, oversized pores are likely to appear in the second coating 313, thereby affecting the contact between the second coating 313 and the electrolyte.

[0074] The structure and composition of the diaphragm are explained above, and the preparation method of the diaphragm will be explained below.

[0075] The preparation method of the diaphragm of the embodiment of the present application may include the following steps: coating a first coating slurry on the surface of one side of a base film; coating a second coating slurry on the surface of the other side of the base film; the first coating slurry and the second coating slurry are different slurries; subjecting the base film coated with the first coating slurry and the second coating slurry to multi-stage extraction, and then obtaining the diaphragm after drying.

[0076] In the obtained diaphragm, the pore size distribution η of the second coating is (2) The pore size distribution η of the first coating (1) Satisfy: η (2) / η (1) >1.0, where η (1) =[D90 (1) -D25 (1) ] / D50 (1) , η (2) =[D90 (2) -D25 (2) ] / D50 (2) ;

[0077] D25 (1) It indicates the pore size corresponding to when the volume percentage of the cumulative pore size distribution in the first coating reaches 25%;

[0078] D50 (1) It indicates the pore size corresponding to when the volume percentage of the cumulative pore size distribution in the first coating reaches 50%;

[0079] D90 (1) It indicates the pore size corresponding to when the volume percentage of the cumulative pore size distribution in the first coating reaches 90%;

[0080] D25 (2)It indicates the pore size corresponding to when the volume percentage of the cumulative pore size distribution in the second coating reaches 25%;

[0081] D50 (2) It indicates the pore size corresponding to when the volume percentage of the cumulative pore size distribution in the second coating reaches 50%;

[0082] D90 (2) It indicates the pore size corresponding to when the volume percentage of the cumulative pore size distribution in the second coating reaches 90%.

[0083] Wherein, the coating slurry may include a first coating slurry and a second coating slurry. The first coating slurry is used to form a first coating. The second coating slurry is used to form a second coating. The organic resins in the first coating slurry and the second coating slurry can both be aramid resins. The aramid resin can be at least one of meta, para or other heterocyclic, modified aramid resins. When preparing the first coating slurry, the organic resin can be first dissolved in one or more good solvents, and then the inorganic particles are dispersed therein to obtain a first coating slurry containing organic resin and inorganic particles. The second coating slurry can be prepared according to the preparation method of the first coating slurry. The good solvent includes, but is not limited to, one or a combination of at least two of N-methylpyrrolidone (N-methylpyrrolidone, NMP), dimethylacetamide (dimethylacetamide, DMAC) or N, N-dimethylformamide (N, N-dimethylformamide, DMF).

[0084] In addition to the organic resin and inorganic particles, the coating slurry may also contain a cosolvent / pore former, and a poor solvent for the organic resin. The cosolvent / pore former includes, but is not limited to, one or a combination of at least two of lithium chloride, magnesium chloride, calcium chloride, calcium carbonate, and calcium chloride. The poor solvent includes, but is not limited to, one or a combination of at least two of water, methanol, ethanol, propanol, acetone, ethyl acetate, dichloromethane, and petroleum ether.

[0085] In the coating slurry, the weight of organic resin accounts for 2-20%, the weight of inorganic particles can be 0-30%, the weight of co-solvent can be 0-8%, the weight of poor solvent can be 0-5%, and the weight of good solvent can be 60-85%. Among them, the amount of organic resin and inorganic particles added in the first coating slurry and the second coating slurry is different. The specific amount can be formulated with reference to the weight content of organic resin and inorganic particles in the composition structure of the diaphragm, and will not be explained one by one here. The first coating slurry and the second coating slurry are coated on both sides of the base film respectively, and then subjected to multi-stage extraction. Among them, the coating slurry can be coated by gravure roller, wire rod, extrusion or dip coating.

[0086] In one embodiment, the multi-stage extraction can be performed in a multi-stage extraction tank. The extraction tank contains a mixed solution of a good solvent and a poor solvent for the organic resin. In the multi-stage extraction, the concentration of the good solvent in different extraction tanks can be different. The poor solvent in the extraction tank can be water.

[0087] The multi-stage extraction tank is at least a three-stage extraction tank, that is, it has three sections. The mass proportion of the good solvent in the first-stage extraction tank is 35-60%, the mass proportion of the good solvent in the second-stage extraction tank is 0-35%, and the mass proportion of the good solvent in the third-stage extraction tank is 0-2.5%. The time of the first-stage extraction and the second-stage extraction is 5 to 15 seconds respectively.

[0088] The concentration of the good solvent is unevenly distributed in the first-stage extraction tank. The concentration of the good solvent gradually decreases in the direction of movement of the base film in the first-stage extraction tank, and the difference between the highest concentration of the good solvent and the lowest concentration of the good solvent in the first-stage extraction tank is 5-15%. The method of controlling the uneven concentration of the good solvent in the first-stage extraction tank can be achieved in many ways, such as setting a baffle in the direction of the base film to slow down the diffusion efficiency of the good solvent in the extraction tank, so that the concentration of the good solvent in each place in the extraction tank is different.

[0089] The diaphragm of the present application will be further described in detail below in conjunction with specific embodiments.

[0090] Example 1

[0091] The preparation method of the diaphragm of this embodiment comprises the following steps:

[0092] S11. Preparation of first coating slurry

[0093] 0.5 kg of calcium chloride, a dissolution aid and pore-forming agent, was added to 8.7 kg of DMAC and stirred thoroughly to dissolve, and then 0.8 kg of meta-aramid powder was added and stirred in a constant temperature water bath at 40°C for 1 hour until the aramid was completely dissolved. 2.4 kg of alumina with a particle size of 0.2 μm was added to 7.6 kg of DMAC, and the alumina dispersion was obtained after sufficient grinding and dispersion. The aramid solution and the alumina dispersion were mixed to prepare the first coating slurry; wherein the mass ratio of aramid to alumina was 1:3.

[0094] S12. Preparation of second coating slurry

[0095] 0.9 kg of calcium chloride, a dissolution aid and pore-forming agent, was added to 15 kg of DMAC and stirred thoroughly to dissolve, and then 1.5 kg of meta-aramid powder was added and stirred in a constant temperature water bath at 40°C for 1 hour until the aramid was completely dissolved. 1.0 kg of alumina with a particle size of 0.5 μm was added to 3 kg of DMAC, and the alumina dispersion was obtained after sufficient grinding and dispersion. The aramid solution and the alumina dispersion were mixed to prepare the second coating slurry; wherein the mass ratio of aramid to alumina was 1.5:1.

[0096] S13. Diaphragm preparation

[0097] Use a gravure roller to apply the first coating slurry and the second coating slurry to both sides of the 7μm PE base film, the upper roller applies the first coating slurry, and the lower roller applies the second coating slurry, and the coating speed is 30m / min. After coating, enter the mixed solution of DMAC and water for curing. The DMAC content in the first extraction tank is 40-50%, the DMAC content in the second extraction tank is 30%, and the DMAC content in the third extraction tank is <2.5%. The time for the diaphragm to pass through each extraction tank is 8S. After washing, use a three-stage oven for drying, and the temperatures of each stage of the oven are 50℃, 55℃, and 60℃ respectively. After drying, a 10μm aramid coating film is obtained. The mass content of aramid in the first coating of the coating film accounts for 25%, and the mass content of aluminum oxide accounts for 75%. The mass content of aramid in the second coating of the coating film accounts for 60%, and the mass content of aluminum oxide accounts for 40%.

[0098] Example 2

[0099] This embodiment is a diaphragm, and the specific preparation method is the same as that of Example 1, except that in the second coating, the mass ratio of aramid to alumina is 7:3, and the alumina particle size D50 is 0.6 μm.

[0100] Example 3

[0101] This embodiment is a diaphragm, and the specific preparation method is the same as that of Example 1, except that in the second coating, the mass ratio of aramid to alumina is 5.5:4.5, and the alumina particle size D50 is 0.4 μm.

[0102] Example 4

[0103] This embodiment is a diaphragm, and the specific preparation method is the same as that of Example 1, except that in the first coating, the mass ratio of aramid to aluminum oxide is 3.5:6.5.

[0104] Example 5

[0105] This embodiment is a diaphragm, and the specific preparation method is the same as that of Example 1, except that in the first coating layer, the particle size of aluminum oxide is 0.4 μm.

[0106] Example 6

[0107] This embodiment is a diaphragm, and the specific preparation method is the same as that of Example 1, except that in the first coating, the inorganic particles are barium sulfate.

[0108] Example 7

[0109] This embodiment is a diaphragm, and the specific preparation method is the same as that of Example 1, except that in the second coating, the mass ratio of aramid to aluminum oxide is 9:1.

[0110] Example 8

[0111] This embodiment is a diaphragm, and the specific preparation method is the same as that of Embodiment 1, except that in the second coating, the aluminum oxide particle size D50 is 1.4 μm.

[0112] Comparative Example 1

[0113] The preparation method of the diaphragm of the comparative example comprises the following steps:

[0114] S11. Preparation of coating slurry

[0115] 0.5 kg of calcium chloride, a dissolution aid and pore-forming agent, was added to 8.7 kg of DMAC and stirred thoroughly to dissolve, and then 0.8 kg of meta-aramid powder was added and stirred in a constant temperature water bath at 40°C for 1 hour until the aramid was completely dissolved. 2.4 kg of alumina with a particle size of 0.2 um was added to 7.6 kg of DMAC, and the alumina dispersion was obtained after sufficient grinding and dispersion. The aramid solution and the alumina dispersion were mixed to prepare a coating slurry.

[0116] S12. Diaphragm preparation

[0117] Use a gravure roller to coat the aramid slurry on both sides of the 7μm PE base film. The upper and lower rollers are both coated with the same coating slurry, and the coating speed is 30m / min. After coating, enter the mixed solution of DMAC and water for curing. The DMAC content in the first extraction tank is 40-50%, the DMAC content in the second extraction tank is 30%, and the DMAC content in the third extraction tank is <2.5%. The time for the diaphragm to pass through each extraction tank is 8S. After washing, use a three-stage oven for drying. The temperatures of each stage are 50℃, 55℃, and 60℃ respectively. After drying, a 10um aramid coating film is obtained, and both sides of the coating film are symmetrical coatings with the same components and pore size distribution.

[0118] Comparative Example 2

[0119] This comparative example is a diaphragm, and the specific preparation method is the same as that of comparative example 1, except that in the coating, the mass ratio of aramid to alumina is 7:3, and the particle size of alumina is 0.5 μm.

[0120] Comparative Example 3

[0121] This comparative example is a diaphragm, and the specific preparation method is the same as that of Example 1, except that in the first coating, the organic resin is PVDF, the mass ratio of the organic resin to alumina is 4:6, and the particle size of the inorganic ion alumina is 0.6 μm. In the second coating, the particle size of the inorganic ion alumina is 0.4 μm.

[0122] Comparative Example 4

[0123] This comparative example is a diaphragm, and the specific preparation method is the same as that of comparative example 1, except that in the first coating, the mass ratio of aramid to alumina is 3.5:6.5, and the alumina particle size is 0.2 μm. In the second coating, the mass ratio of organic resin to alumina is 5.5:4.5, and the particle size of inorganic ion alumina is 0.4 μm.

[0124] Among them, during the preparation process of the diaphragms of each embodiment and comparative example, the dissolution mixing time, the addition amount of good solvent and poor solvent, the extraction process parameters, and the drying process parameters can be adjusted accordingly according to the specific material composition and ingredients to match the relevant process parameters with the raw material composition.

[0125] The composition parameters of the diaphragms of Examples 1-8 and Comparative Examples 1-4 are listed in Table 1.

[0126] Lithium-ion batteries were assembled using the separators of Examples 1-8 and Comparative Examples 1-4. The specific assembly process included the following steps:

[0127] S21. Production of positive electrode

[0128] The positive electrode active material lithium iron phosphate, conductive agent carbon black, and adhesive polyvinylidene difluoride (PVDF) are mixed with NMP solvent at a mass ratio of 96.5:1.0:2.5, stirred evenly to form a positive electrode slurry, and the positive electrode slurry is evenly coated on both sides of the aluminum foil using a coating device, and the NMP solvent is removed after drying in an oven. The coated pole piece is made into a positive electrode piece after cold pressing, striping, and pole ear welding.

[0129] S22, negative electrode sheet production

[0130] The negative electrode active material artificial graphite, conductive agent SP, thickener carboxymethylcellulose (CMC), and adhesive polymerized styrene butadiene rubber (SBR) are stirred and evenly mixed in deionized water at a weight ratio of 96:1.0:1.5:1.5 to form a negative electrode slurry. The negative electrode slurry is evenly coated on both sides of the copper foil using a coating device. The electrode sheet after oven drying is subjected to cold pressing, striping, and ear welding processes to form a negative electrode sheet.

[0131] S23, winding the positive electrode sheet, separator and negative electrode sheet together to form a bare cell, wherein the first coating of the separator is arranged toward the positive electrode sheet, and the second coating is arranged toward the negative electrode sheet. The bare cell is then packaged, baked, injected, left to stand, formed, exhausted, and measured to form a lithium-ion battery.

[0132] The pore size distribution of each embodiment and comparative example diaphragm and the thermal performance and cycle performance of the corresponding lithium ion battery were tested respectively. The test results are listed in Table 1. The specific test process of the pore size distribution test, battery hot box test and cycle performance test is as follows.

[0133] 1. Pore size distribution test

[0134] 1) Divide a roll of separator into three equal parts in the TD and MD directions to form a nine-square grid. Randomly select and cut a sample of 1 cm*1 cm in size from each grid, for a total of 9 samples;

[0135] 2) Use SEM to take pictures of the cross section of each sample and select the pictures at a magnification of 20K;

[0136] 3) For each sample, the cross-section and surface electron microscopy selected a 5.0μm*1.5μm rectangular area, and the entire area was divided into 500*150 pixels, each pixel was 10nm long and 100nm in area. 2 The color level of each pixel is identified and summarized. A is the maximum color level of the area, and B is the minimum color level of the area. The color level value of any pixel in the area is an:

[0137] C=(an-B) / (AB)×100%,

[0138] Wherein, C is the discrimination value of the pixel point. If C<40%, the pixel point is identified as a hole structure, otherwise it is identified as a boundary structure.

[0139] The above judgment is performed on all pixels in the entire area. All pore structures and boundary structure distributions are distinguished. For a closed area surrounded by a boundary structure, it is judged as a pore. The area of ​​the pore containing the pixels is the pore area S. The pore diameter d is calculated as:

[0140] d=2*(S / π)^0.5

[0141] 4) The cross-sectional pore sizes of the nine samples were accumulated to produce a cross-sectional pore size distribution diagram. D50 is the pore size when the cumulative volume of all pore sizes of the nine samples is 50%.

[0142] 2. Battery hot box test:

[0143] After the battery is fully charged in the standard charging mode, the test is carried out within 12 to 24 hours. The battery is heated by convection or circulating hot air oven at a starting temperature of 25±3℃, a temperature change rate of 5±2℃ / min, and the temperature is raised to 180±2℃. The test is terminated after 30 minutes. The battery passes the test if it does not catch fire or explode.

[0144] 3. Cycle performance test:

[0145] After the battery cell is tested for core capacity at 0.2C at 25°C, it is discharged to 2.5V at a constant current and left to stand for 30 minutes;

[0146] The battery cell was placed in a 55°C environment for 4 hours; the battery was cycled according to the following steps, and the capacity retention rate after 1000 cycles was calculated: 0.5C constant current and constant voltage charging to 3.65V / 0.05C cut-off, standing for 30 minutes, and 0.5C constant current discharging to 2.5V and standing for 30 minutes.

[0147] Table 1

[0148]

[0149]

[0150] Table 1 (continued)

[0151]

[0152] It can be seen from the data in Table 1 that both sides of Comparative Example 1 and Comparative Example 2 have coatings with the same composition and structure. In the lithium-ion batteries corresponding to the separators of Comparative Example 1 and Comparative Example 2, new SEI films are repeatedly generated on the surface of the negative electrode materials during the cycle, thereby continuously consuming the electrolyte. Therefore, the side of the separator close to the negative electrode plate is more likely to be depleted of liquid, which in turn forms a broken bridge of the electrolyte between the negative electrode plate and the separator, thereby causing the battery cell cycle life to decay and reducing the capacity retention rate of the lithium-ion battery after 100 cycles.

[0153] In Comparative Example 2, the coatings on both sides of the diaphragm use the same coating formula, and the coatings on both sides use inorganic particles with larger particle size (0.5um) and lower content (30%). The coatings formed are not dense, and the thermal shrinkage of the diaphragm will be large, which is not conducive to the safety performance of the battery cell. At the same time, the pore structure and pore distribution of the coatings on both sides of the diaphragm are the same, and the negative electrode side will still lack liquid in the later stage of the cycle, resulting in poor cycle performance.

[0154] The capacity retention rates of the lithium-ion batteries corresponding to Examples 1-8 of the present application after 100 cycles are all higher than those of Comparative Examples 1-2. This indicates that when the coatings on both sides of the diaphragm meet the requirements defined in the present application, its cycle life can be significantly improved.

[0155] It can be seen from the relevant test data of Examples 1-8 that the capacity retention rate of Example 2 is better than that of Example 1, Example 4 and Example 6, and is better than that of Example 3, Example 5 and Example 8, and the data of Example 7 is relatively low. This indicates that the cycle life of the lithium-ion battery can be improved by optimizing the pore size distribution ratio of the first coating layer and the second coating layer.

[0156] In addition, it can be seen from the comparative data of Examples 1-8 and Example 9 that in Example 9, although the pore size distribution ratio of the second coating layer and the first coating layer of the diaphragm satisfies η (2) / η (1) >1.0, however, due to the pore size D90 of the second coating of the diaphragm (2) Smaller than the pore size D90 of the first coating (1) , and the effect of Examples 1-8 of the present application cannot be achieved. The main reason may be that when the pore size D90 of the second coating is (2) Smaller than the pore size D90 of the first coating (1) When the electrolyte is retained by the second coating, the electrolyte retention capacity of the second coating is insufficient. In the later stage of the battery cycle, the electrolyte on the side of the diaphragm facing the negative electrode plate cannot be effectively replenished, resulting in a decrease in the capacity retention rate of the lithium-ion battery.

[0157] In Comparative Example 4, the ratio of the pore size distribution of the second coating layer to the first coating layer does not satisfy η (2) / η (1) >1.0. The corresponding capacity retention rate of the lithium-ion battery is also low. This indicates that when the pore size distribution ratio of the first coating layer to the second coating layer does not meet the range value specified in the present application, it is insufficient to make the second coating layer always wetted by the electrolyte, thereby causing a decrease in the cycle performance of the lithium-ion battery.

[0158] In summary, in the diaphragm of the present application, by optimizing the content of organic resin in the first coating and the second coating and the particle size of inorganic particles, the second coating has a higher organic resin content relative to the first coating, and the inorganic particles with larger particle size can help the second coating to obtain a wider pore size distribution relative to the first coating, thereby achieving an asymmetric distribution of pore size and an asymmetric distribution of electrolyte, and the electrolyte is more enriched in the second coating. The small-sized inorganic particles in the first coating can make the diaphragm position higher in heat resistance. Therefore, the diaphragm of the embodiment of the present application can obtain a longer cycle life on the basis of having higher heat resistance.

[0159] The above are only specific implementations of the present application, but the protection scope of the present application is not limited thereto. Any technician familiar with the technical field can easily think of changes or substitutions within the technical scope disclosed in the present application, which should be included in the protection scope of the present application. Therefore, the protection scope of the present application should be based on the protection scope of the claims.

Claims

1. A diaphragm, characterized in that: It includes a base film, a first coating layer and a second coating layer, wherein the first coating layer and the second coating layer are respectively arranged on both sides of the base film; The pore size distribution η of the second coating (2) The pore size distribution η of the first coating (1) Satisfy: η (2) / η (1) >1.0, where or (1) =[D90 (1) -D25 (1) ] / D50 (1) ,or (2) =[D90 (2) -D25 (2) ] / D50 (2) ; D25 (1) It indicates the pore size corresponding to when the volume percentage of the cumulative pore size distribution in the first coating reaches 25%; D50 (1) It indicates the pore size corresponding to when the volume percentage of the cumulative pore size distribution in the first coating reaches 50%; D90 (1) It indicates the pore size corresponding to when the volume percentage of the cumulative pore size distribution in the first coating reaches 90%; D25 (2) It indicates the pore size corresponding to when the volume percentage of the cumulative pore size distribution in the second coating reaches 25%; D50 (2) It indicates the pore size corresponding to when the volume percentage of the cumulative pore size distribution in the second coating reaches 50%; D90 (2) It indicates the pore size corresponding to when the volume percentage of the cumulative pore size distribution in the second coating reaches 90%.

2. The diaphragm according to claim 1, characterized in that The pore size D90 of the second coating (2) Larger than the pore size D90 of the first coating (1) .

3. The diaphragm according to claim 2, characterized in that The pore size D90 of the first coating (1) The pore size D90 of the second coating is less than 0.8 μm. (2) Greater than or equal to 0.5μm.

4. The diaphragm according to claim 3, characterized in that The pore size D90 of the first coating (1) The pore size D90 of the second coating is 0.1-0.5 μm. (2) 0.6~2μm.

5. The diaphragm according to any one of claims 1 to 4, characterized in that: The η (2) / η (1) The value ranges from 1.2 to 3.

6. The diaphragm according to any one of claims 1 to 5, characterized in that: The first coating and the second coating both include organic resin; wherein the mass content of the organic resin in the first coating accounts for less than 50% of the total mass of the first coating, and the mass content of the organic resin in the second coating accounts for a greater proportion of the total mass of the second coating than the mass content of the organic resin in the first coating.

7. The diaphragm according to claim 6, characterized in that The mass content of the organic resin in the first coating layer is 10-30%, and the mass content of the organic resin in the second coating layer is 20-80%.

8. The diaphragm according to claim 6 or 7, characterized in that: The content of the organic resin in the second coating layer is 1.2 to 5 times the content of the organic resin in the first coating layer.

9. The diaphragm according to any one of claims 6 to 8, characterized in that: The first coating layer and the second coating layer both include inorganic particles; the particle size D50 of the inorganic particles in the first coating layer is 0.05 to 0.6 μm, and the particle size D50 of the inorganic particles in the second coating layer is 0.2 to 2 μm.

10. The diaphragm according to claim 9, characterized in that The particle size D50 of the inorganic particles in the second coating layer and the particle size D50 of the inorganic particles in the first coating layer are 1.5 to 5.

11. A method for preparing a diaphragm, characterized in that: include: Applying a first coating slurry on one side of the base film; Applying a second coating slurry on the other side surface of the base film; The first coating slurry and the second coating slurry are different slurries; The base film coated with the first coating slurry and the second coating slurry is subjected to multi-stage extraction, and then dried to obtain the separator; In the obtained diaphragm, the pore size distribution η of the second coating is (2) The pore size distribution η of the first coating (1) Satisfy: η (2) / η (1) >1.0, where or (1) =[D90 (1) -D25 (1) ] / D50 (1) ,or (2) =[D90 (2) -D25 (2) ] / D50 (2) ; D25 (1) It indicates the pore size corresponding to when the volume percentage of the cumulative pore size distribution in the first coating reaches 25%; D50 (1) It indicates the pore size corresponding to when the volume percentage of the cumulative pore size distribution in the first coating reaches 50%; D90 (1) It indicates the pore size corresponding to when the volume percentage of the cumulative pore size distribution in the first coating reaches 90%; D25 (2) It indicates the pore size corresponding to when the volume percentage of the cumulative pore size distribution in the second coating reaches 25%; D50 (2) It indicates the pore size corresponding to when the volume percentage of the cumulative pore size distribution in the second coating reaches 50%; D90 (2) It indicates the pore size corresponding to when the volume percentage of the cumulative pore size distribution in the second coating reaches 90%.

12. The preparation method according to claim 11, characterized in that: The multi-stage extraction includes three-stage extraction, the mass proportion of good solvent in the first-stage extraction is 35-60%, the mass proportion of good solvent in the second-stage extraction tank is 0-35%, and the mass proportion of good solvent in the third-stage extraction tank is 0-2.5%.

13. The preparation method according to claim 12, characterized in that: In the first stage extraction, the concentration of the good solvent gradually decreases in the moving direction of the base film in the first extraction tank, and the difference between the highest concentration of the good solvent and the lowest concentration of the good solvent in the first extraction tank is 0.1-15%.

14. The preparation method according to claim 12 or 13, characterized in that: The time of the first stage extraction and the second stage extraction are respectively 5 to 15 seconds.

15. A battery, characterized in that: It includes a positive electrode sheet, a negative electrode sheet, an electrolyte and a diaphragm as described in any one of claims 1 to 10, wherein the diaphragm is arranged between the positive electrode sheet and the negative electrode sheet, and the first coating of the diaphragm is arranged toward the positive electrode sheet, the second coating of the diaphragm is arranged toward the negative electrode sheet, and the electrolyte impregnates the diaphragm.

16. An electrical equipment, characterized in that: Comprising the battery of claim 15.

Citation Information

Cited By

  • Separator, electrochemical device, and electronic device

    CN121460871A